Formulation, Characterization and In-vitro Sun Protection Factor of a Lemongrass Sunscreen Lotion: Sun Protection Factor of a Lemongrass Sunscreen Lotion - Yaseen, Mariam; Mahmood, Tariq; Yousaf, Abid M.; Shahzad, Yasser; Bjørklund, Geir; Lysiuk, Roman (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2018)
Sunburn, pigmentation disorders, photocarcinogenesis, immunosuppression and other skin related damages are caused by the ultraviolet radiation present in the sunlight. The aim of this study was to determine the sun protection factor (SPF) value of the lemongrass extract, also the formation of its stable sunscreen lotion and to determine its SPF value. For the determination of SPF value of the developed formulation, spectrophotometric method was used along with Mansur equation. The SPF value of lemongrass sunscreen lotion was 22 with the antioxidant potential of 94.20%. The hydrogen ion concentration (pH) of the lotion was 5.5, which complied with skin pH. Viscosity profile of lotion indicated good rheology which is an important aspect of a formulation during application. The formulation was stable as there was no phase separation observed after centrifugation, freeze-thaw and thermal stress tests. Harmful effects of chemicals are evident and therefore, the natural source could become a good, economical, easily accessible and safe alternative formulation ingredient in sunscreen products due to its beneficial effects and safety.